A naturalização da precariedade: das desigualdades socioeconômicas às educacionais - Silva Júnior, Silvio Roberto Dias da (2024)
This work hopes to help think critically about the materialization of Brazilian educational inequality. Methodologically, it is a Case Study with praxiological intentions that discusses the structuring and structured structure of Brazilian educational inequality through the analysis of the daily practices of a public basic education school ranked among the lowest indices in Fortaleza (CE) in IDEB 2017 and ENEM 2018, and located in the neighborhood that had some of the lowest social and economic indicators in the municipality. Taking as references the reproduction of cultural domination and the inequality of opportunities in neoliberal capitalism (Bourdieu and Passeron, 1992; Bourdieu, 1994, 1996, 2004, 2007, 2013), Brazilian educational inequalities and their consequences (Algebaile, Herckert and Valla, 2008; Algebaile, 2003, 2009, 2013a, 2013b; Beserra and Lavergne, 2018) and the naturalization of inequality of opportunities in peripheral modernity (Souza, 2000, 2002, 2006, 2011), The research's main objective is to demonstrate how what is precarious is naturalized on the periphery of the capitalist system, how culture, despite being changeable in time and space, tends to be preserved if it is not understood and transformed through the way individuals perceive it. and interpret reality and how an institutional culture is materialized on a daily basis, highlighting the symbolic failure of a State that does not fulfill what it promises: it does not properly train teachers, does not offer citizenship to the poorest citizens and reproduces, through the practices of agents – in which does not intervene – a culture that, precisely for this reason, does not question nor intend to transform. Finally, it argues that Brazilian educational inequality is the historical materialization of the public policies of the Brazilian State and the practices of its agents, all socially naturalized by Brazilians without due critical-reflective analysis and, for this very reason, incapable of being understood, perhaps transformed.